Glass fiber reinforced nylon composite material as well as preparation method and application thereof
By adding specific components to glass fiber reinforced nylon composites, the problem of degradation of material forming fluidity and toughness is solved, and the comprehensive performance of high flowability, high toughness and mechanical strength is achieved, expanding the application range and reducing production costs.
Patent Information
- Application Number
- CN202411869299.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-04
AI Technical Summary
While the existing glass fiber reinforced nylon composite materials increase mechanical strength, their forming fluidity and toughness will decrease, resulting in problems such as low strength of the fusion marks of the parts and difficulty in forming.
The composite material is formed by adding specific contents of glass fibers to nylon and glass fibers to expose absorbers, dispersants, tougheners and black masters, which improve the fluidity and toughness of the material.
It is achieved to improve the flowability and toughness of composite materials while ensuring mechanical strength, overcome the problems of poor flowability and toughness in the prior art, reduce production costs, and expand the scope of application.
Smart Images

Figure BDA0005195353390000021 
Figure BDA0005195353390000101 
Figure BDA0005195353390000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer composite materials, and in particular to a glass fiber reinforced nylon composite material and a preparation method and application thereof. Background Art
[0002] Nylon (PA) is the earliest developed and most widely used thermoplastic engineering plastic, but due to its high water absorption and easy deformation after absorbing water, it affects the dimensional stability of the product, thereby limiting its application in areas with high mechanical strength and dimensional precision requirements. In order to improve the above shortcomings, expand its application areas, and better meet the requirements for performance, the industry generally adopts glass fiber reinforcement modification of nylon to achieve the purpose of reducing the water absorption of the material and improving the dimensional stability and mechanical strength of the material.
[0003] Glass fiber reinforced nylon materials have good properties such as high strength, high heat resistance, high fatigue resistance, and low forming shrinkage, so they are widely used in the fields of automobiles, machinery, home appliances, and power tools. However, although the introduction of glass fiber can improve the rigidity of the material and reduce the water absorption of the material, as its content in the composite material system increases, especially when the glass fiber content in the fiber-reinforced PA6 material is high, the toughness of the resulting material will decrease, and the molding fluidity will also be greatly damaged, which is disadvantageous for large parts, thereby causing a series of problems such as low strength of the weld mark of the part and difficulty in forming the part.
[0004] CN106916443A discloses a heat-conducting nylon plastic and a method for preparing the heat-conducting nylon plastic. The heat-conducting nylon plastic uses two materials, polyamide elastomer and polyolefin elastomer, as toughening agents to increase the toughness of the heat-conducting nylon plastic, making the material not easy to break and having high impact strength. However, due to the high content of aluminum oxide, the interfacial bonding between glass fiber and PA6 is affected, resulting in a decrease in the mechanical properties of the material, and also affecting its processing and forming properties. CN101983988B discloses a polyamide 6 composite material and a preparation method thereof, which uses spinning-grade polyamide 6 resin as a fluidity improver to improve the fluidity of the composite material. However, the addition of a higher content of spinning-grade polyamide 6 resin will increase production costs.
[0005] Therefore, it is of great significance to design and develop a high-fluidity, high-toughness glass fiber reinforced nylon composite material. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a glass fiber reinforced nylon composite material and its preparation method and application. The composite material has high fluidity and high toughness while ensuring good mechanical strength, and can overcome the technical shortcomings of the prior art in which the molding fluidity and toughness are deteriorated in the process of improving glass fiber reinforced nylon, which leads to low fusion mark strength of the product and difficulty in product molding.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a glass fiber reinforced nylon composite material, wherein the raw materials for preparing the glass fiber reinforced nylon composite material include the following components in parts by weight:
[0009]
[0010] The present invention compounds glass fiber exposed absorbent, dispersant, toughening agent and black masterbatch, and adds them to glass fiber reinforced nylon material composed of nylon and glass fiber. The present invention can effectively overcome the technical defects in the prior art that glass fiber improves the mechanical strength of nylon composite materials but leads to poor molding fluidity and toughness, thereby making the strength of the fusion mark of the product too low and the product difficult to mold, thereby obtaining a high-fluidity and high-toughness glass fiber reinforced nylon composite material, thereby expanding its application range.
[0011] In the present invention, the content of nylon is 50-80 parts by weight, for example, it can be 52 parts by weight, 55 parts by weight, 58 parts by weight, 60 parts by weight, 62 parts by weight, 65 parts by weight, 68 parts by weight, 70 parts by weight, 75 parts by weight or 78 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0012] The content of modified glass fiber is 10-40 parts by weight, for example, it can be 12 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 28 parts by weight, 30 parts by weight, 32 parts by weight, 35 parts by weight or 38 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0013] The content of exposed absorbent of glass fiber is 0.1-0.5 weight part, for example, it can be 0.12 weight part, 0.15 weight part, 0.18 weight part, 0.2 weight part, 0.25 weight part, 0.3 weight part, 0.35 weight part, 0.4 weight part or 0.45 weight part, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0014] In the present invention, the addition of a specific amount of glass fiber exposure absorbent can significantly improve the fluidity of nylon and effectively improve the glass fiber exposure problem of the obtained glass fiber reinforced nylon composite material. When its content is less than 0.1 parts by weight, the fluidity of the obtained product cannot be well improved. When its content is higher than 0.5 parts by weight, the fluidity is too high, which is not conducive to its injection molding and also affects its mechanical properties.
[0015] The content of dispersant is 0.2-0.5 parts by weight, for example, it can be 0.25 parts by weight, 0.28 parts by weight, 0.3 parts by weight, 0.32 parts by weight, 0.35 parts by weight, 0.38 parts by weight, 0.4 parts by weight, 0.42 parts by weight or 0.45 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0016] The content of the toughening agent is 2-5 parts by weight, for example, it can be 2.2 parts by weight, 2.5 parts by weight, 2.8 parts by weight, 3.0 parts by weight, 3.2 parts by weight, 3.5 parts by weight, 4.0 parts by weight, 4.5 parts by weight or 4.8 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0017] The content of the black masterbatch is 0.4-2 parts by weight, for example, it can be 0.42 parts by weight, 0.45 parts by weight, 0.5 parts by weight, 0.8 parts by weight, 1.0 parts by weight, 1.2 parts by weight, 1.4 parts by weight, 1.6 parts by weight or 1.8 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the said range.
[0018] In the present invention, the addition of a specific content of black masterbatch is beneficial to improving the toughness and fluidity of the glass fiber reinforced nylon composite material, while also ensuring the excellent quality of the appearance surface of the glass fiber reinforced nylon composite material. Further, when the mass ratio of the nylon glass fiber exposed absorbent to the black masterbatch is 1:(2-10), the obtained glass fiber reinforced nylon composite material has good comprehensive properties.
[0019] The content of the auxiliary agent is 0.3-1.8 parts by weight, for example, it can be 0.5 parts by weight, 0.8 parts by weight, 1.0 parts by weight, 1.2 parts by weight, 1.4 parts by weight, 1.6 parts by weight or 1.8 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0020] In the present invention, a high-fluidity and high-toughness glass fiber reinforced nylon composite material can be obtained by adding only a small amount of glass fiber exposed absorbent, dispersant, toughening agent and black masterbatch and other components, thereby helping to reduce production costs and further improve its market competitiveness.
[0021] Preferably, the mass ratio of the exposed absorbent, dispersant and toughening agent of the nylon glass fiber is 1:(1-4):(10-25), for example, it can be 1:1:10, 1:2:15, 1:3:20 or 1:4:25, etc., as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0022] The nylon glass fiber exposed absorbent, dispersant and toughening agent in the present invention can produce a synergistic effect. Through the cooperation of the three, the dispersibility of each raw material component can be significantly improved, the agglomeration of glass fiber in nylon is effectively reduced, and the friction between glass fiber and nylon is also reduced. While ensuring a certain mechanical strength, the toughness and fluidity of the glass fiber reinforced nylon composite material can be well improved, thereby obtaining a product with excellent comprehensive performance. Furthermore, when the mass ratio of the nylon glass fiber exposed absorbent, dispersant and toughening agent is 1:(1-4):(10-25), the obtained glass fiber reinforced nylon composite material has good comprehensive performance.
[0023] Preferably, the glass fiber exposed absorbent includes any one of ethylene bisstearic acid amide, modified ethylene bis fatty acid amide or polytetrafluoroethylene, or a combination of at least two thereof, and more preferably modified ethylene bis fatty acid amide.
[0024] Preferably, the dispersant includes any one of a fatty acid dispersant, a pentaerythritol ester dispersant or a silicone dispersant, or a combination of at least two of them, and more preferably a silicone dispersant.
[0025] The addition of the dispersant in the present invention can effectively improve the dispersibility of each raw material component, thereby being beneficial to improving the fluidity and toughness of the glass fiber reinforced nylon composite material.
[0026] Preferably, the toughening agent includes any one or a combination of at least two of polyolefin elastomer (POE), styrene-butadiene-styrene block copolymer (SBS), ethylene propylene diene monomer (EPDM), methacrylate / butadiene / styrene copolymer (MBS) or maleic anhydride grafted polyolefin elastomer, and is further preferably maleic anhydride grafted polyolefin elastomer.
[0027] The addition of the toughening agent in the present invention can significantly improve the toughness of the glass fiber reinforced nylon composite material, making the material less prone to breakage and having good impact resistance.
[0028] Preferably, the black masterbatch includes an organic black masterbatch and / or an inorganic black masterbatch, and is more preferably an organic black masterbatch.
[0029] Preferably, the organic black masterbatch includes Nanjing Weishang S-06; its use can improve the dispersibility and compatibility between the various raw material components, thereby improving the fluidity of the obtained material.
[0030] Preferably, the viscosity of the nylon is 2.45-2.55, for example, it can be 2.45, 2.462.47, 2.48, 2.49, 2.5, 2.51, 2.52, 2.53, 2.54 or 5.55, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0031] Preferably, the nylon comprises REMIF M1013B.
[0032] Preferably, the modified glass fiber is glass fiber treated with a coupling agent.
[0033] The present invention uses glass fiber treated with a coupling agent, which can effectively enhance the compatibility and adhesion between the glass fiber and nylon, which can not only avoid the occurrence of floating fiber problems, but also help to improve the rigidity and strength of the material.
[0034] Preferably, the coupling agent comprises a silane coupling agent.
[0035] Preferably, the silane coupling agent includes γ-aminopropyltriethoxysilane (KH550).
[0036] Preferably, the diameter of the glass fiber is 11-17 μm, for example, it can be 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm or 17 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0037] Preferably, the length of the glass fiber is 13 μm.
[0038] Preferably, the auxiliary agent includes an antioxidant and a lubricant.
[0039] Preferably, the antioxidant comprises a hindered phenol antioxidant and / or a phosphite antioxidant.
[0040] Preferably, the hindered phenol antioxidant includes antioxidant 1010 and / or antioxidant 1098.
[0041] Preferably, the phosphite antioxidant includes antioxidant 168.
[0042] Preferably, the content of the antioxidant is 0.1-0.8 parts by weight, for example, it can be 0.15 parts by weight, 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 0.6 parts by weight or 0.7 parts by weight, as well as specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0043] Preferably, the lubricant comprises stearamide.
[0044] In the present invention, the addition of lubricant can further improve the dispersibility, and can also reduce the friction heat during the material extrusion and processing and improve the demoulding property during injection molding.
[0045] Preferably, the content of the lubricant is 0.2-1 parts by weight, for example, it can be 0.22 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight or 0.95 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0046] In a second aspect, the present invention provides a method for preparing the glass fiber reinforced nylon composite material as described in the first aspect, the preparation method comprising the following steps:
[0047] The glass fiber reinforced nylon composite material is obtained by mixing nylon, glass fiber exposed absorbent, dispersant, toughening agent, black masterbatch and auxiliary agent, adding modified glass fiber, melting and extruding, and granulating.
[0048] Preferably, the nylon, glass fiber exposed absorbent, dispersant, toughening agent, black masterbatch and additives are dried before mixing.
[0049] Preferably, the drying temperature is 75-85°C, for example, it can be 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0050] Preferably, the drying time is 1-2h, for example, it can be 1h, 1.2h, 1.4h, 1.5h, 1.6h, 1.8h or 2h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0051] Preferably, the mixing temperature is 20-30°C, for example, it can be 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C or 29°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0052] Preferably, the mixing is performed under stirring.
[0053] Preferably, the stirring time is 2-3 min, for example, it can be 2 min, 2.2 min, 2.4 min, 2.6 min, 2.8 min or 3 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0054] Preferably, the melt extrusion is carried out in a twin-screw extruder.
[0055] Preferably, the temperature settings of the heating zones of the twin-screw extruder are: zone 1 260-265°C (for example, 260°C, 261°C, 262°C, 263°C, 264°C or 265°C), zone 250-260°C (for example, 250°C, 252°C, 254°C, 256°C, 258°C or 260°C, etc.), zone 3 250-260°C (for example, 250°C, 252°C, 254°C, 256°C, 258°C or 260°C, etc.), zone 4 240-250°C (for example, 240°C, 242°C, 244°C, 246°C, 248°C or 250°C, etc.), zone 5 240-250°C ( For example, it can be 240℃, 242℃, 244℃, 246℃, 248℃ or 250℃, etc.), six zones 230-240℃ (for example, it can be 230℃, 232℃, 234℃, 236℃, 238℃ or 240℃, etc.), seven zones 230-240℃ (for example, it can be 230℃, 232℃, 234℃, 236℃, 238℃ or 240℃, etc.), eight zones 230-240℃ (for example, it can be 230℃, 232℃, 234℃, 236℃, 238℃ or 240℃, etc.), nine zones 230-235℃ (for example, it can be 230℃, 231℃, 232℃, 233℃, 234℃ or 245℃).
[0056] Preferably, the main engine speed of the twin-screw extruder is 450-520rpm, for example, it can be 455rpm, 460rpm, 465rpm, 470rpm, 475rpm, 480rpm, 490rpm, 500rpm, 510rpm or 515rpm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0057] Preferably, the main engine current of the twin-screw extruder is 130-180A, for example, it can be 135A, 140A, 145A, 150A, 155A, 160A, 165A, 170A or 175A, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0058] Exemplarily, the preparation method of the glass fiber reinforced nylon composite material provided by the present invention specifically comprises the following steps:
[0059] (1) Dry PA6, glass fiber exposed absorbent, dispersant, toughening agent, black masterbatch and additives at 80°C for 2 hours;
[0060] (2) The dried raw materials in step (1) are dry-mixed in a high-speed mixer at 20-30°C for 2 minutes, then added to a twin-screw extruder, mixed with modified glass fibers (diameter 11-17 μm) whose surfaces are treated with coupling agents, melt-extruded at 230-265°C, and granulated to prepare the glass fiber reinforced nylon composite material. The temperature settings of the heating zones of the screw are: zone 1 260-265°C, zone 2 250-260°C, zone 3 250-260°C, zone 4 240-250°C, zone 5 240-250°C, zone 6 230-240°C, zone 7 230-240°C, zone 8 230-240°C, zone 9 230-235°C; the main engine speed is 450-520rpm, and the main engine current is 130-180A.
[0061] In a third aspect, the present invention provides an application of the glass fiber reinforced nylon composite material as described in the first aspect in electric tools and automobile parts.
[0062] Compared with the prior art, the present invention has at least the following beneficial effects:
[0063] The present invention can effectively overcome the technical defects in the prior art that the glass fiber improves the mechanical strength of the nylon composite material while causing poor molding fluidity and toughness, thereby making the strength of the weld mark of the product too low and the product difficult to mold, by compounding the glass fiber exposed absorbent, dispersant, toughening agent and black masterbatch, and adding them to the glass fiber reinforced nylon material composed of nylon and glass fiber. At the same time, the present invention realizes that a high-fluidity and high-toughness glass fiber reinforced nylon composite material can be obtained by adding only a small amount of glass fiber exposed absorbent, dispersant, toughening agent and black masterbatch, which not only has a simple preparation process and convenient operation, but also effectively reduces the production cost, thereby expanding the application field of the nylon composite material, and has a strong practical value. DETAILED DESCRIPTION
[0064] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0065] The raw materials used in the following examples are all commercially available, and some of the raw material information is as follows:
[0066] PA6: Ruimeifu M1013B;
[0067] Glass fiber: Jushi fiberglass E6CR13-03-568H;
[0068] Glass fiber exposed absorbent: Weishang WS-600;
[0069] Hyperdispersant: TEGOMER E525;
[0070] Organic black masterbatch: Weishang S-06;
[0071] Toughening agent: Weishang WS-8300;
[0072] Lubricant: Yongying TR044;
[0073] Antioxidant: Lianlong 1098 / 168 (mass ratio is 1:1).
[0074] Example 1
[0075] This embodiment provides a glass fiber reinforced nylon composite material, the raw materials for preparing the composite material include the following components in parts by weight:
[0076]
[0077] The preparation method of the glass fiber reinforced nylon composite material comprises the following steps:
[0078] (1) Dry PA6, glass fiber exposed absorbent, super dispersant, toughening agent, organic black masterbatch, antioxidant and lubricant at 80°C for 2 hours;
[0079] (2) The dried raw materials in step (1) are dry-mixed in a high-speed mixer at 25°C for 2 minutes, then added to a twin-screw extruder, mixed with modified glass fiber (diameter 15 μm) whose surface is treated with coupling agent KH550, melt-extruded at 230-265°C, and granulated to prepare the glass fiber reinforced nylon composite material. The temperature settings of each heating zone of the screw are: zone 1 265°C, zone 2 260°C, zone 3 250°C, zone 4 250°C, zone 5 245°C, zone 6 240°C, zone 7 240°C, zone 8 235°C, zone 9 230°C; the main engine speed is 450rpm, and the main engine current is 148.5A.
[0080] Example 2
[0081] This embodiment provides a glass fiber reinforced nylon composite material, the raw materials for preparing the composite material include the following components in parts by weight:
[0082]
[0083] The preparation method of the glass fiber reinforced nylon composite material comprises the following steps:
[0084] (1) Dry PA6, glass fiber exposed absorbent, super dispersant, toughening agent, organic black masterbatch, antioxidant and lubricant at 75°C for 2 hours;
[0085] (2) The dried raw materials in step (1) are dry-mixed in a high-speed mixer at 20°C for 3 minutes, then added to a twin-screw extruder, mixed with modified glass fiber (diameter 15 μm) whose surface is treated with coupling agent KH550, melt-extruded at 230-265°C, and granulated to prepare the glass fiber reinforced nylon composite material. The temperature settings of each heating zone of the screw are: zone 1 265°C, zone 2 260°C, zone 3 250°C, zone 4 250°C, zone 5 245°C, zone 6 240°C, zone 7 240°C, zone 8 235°C, zone 9 230°C; the main engine speed is 450rpm, and the main engine current is 150.7A.
[0086] Example 3
[0087] This embodiment provides a glass fiber reinforced nylon composite material, the raw materials for preparing the composite material include the following components in parts by weight:
[0088]
[0089] The preparation method of the glass fiber reinforced nylon composite material comprises the following steps:
[0090] (1) Dry PA6, glass fiber exposed absorbent, super dispersant, toughening agent, organic black masterbatch, antioxidant and lubricant at 85°C for 1 hour;
[0091] (2) The dried raw materials in step (1) are dry-mixed in a high-speed mixer at 30°C for 2 minutes, then added to a twin-screw extruder, mixed with modified glass fiber (diameter 15 μm) whose surface is treated with coupling agent KH550, melt-extruded at 230-265°C, and granulated to prepare the glass fiber reinforced nylon composite material. The temperature settings of each heating zone of the screw are: 265°C for zone 1, 260°C for zone 2, 250°C for zone 3, 250°C for zone 4, 245°C for zone 5, 240°C for zone 6, 240°C for zone 7, 235°C for zone 8, and 230°C for zone 9; the main engine speed is 450rpm, and the main engine current is 139.6A.
[0092] Example 4
[0093] This embodiment provides a glass fiber reinforced nylon composite material, the raw materials for preparing the composite material include the following components in parts by weight:
[0094]
[0095] The preparation method of the glass fiber reinforced nylon composite material comprises the following steps:
[0096] (1) Dry PA6, glass fiber exposed absorbent, super dispersant, toughening agent, organic black masterbatch, antioxidant and lubricant at 80°C for 2 hours;
[0097] (2) The dried raw materials in step (1) are dry-mixed in a high-speed mixer at 25°C for 2 minutes, then added to a twin-screw extruder, mixed with modified glass fiber (diameter 15 μm) whose surface is treated with coupling agent KH550, melt-extruded at 230-265°C, and granulated to prepare the glass fiber reinforced nylon composite material. The temperature settings of each heating zone of the screw are: zone 1 265°C, zone 2 260°C, zone 3 250°C, zone 4 250°C, zone 5 245°C, zone 6 240°C, zone 7 240°C, zone 8 235°C, zone 9 230°C; the main engine speed is 450rpm, and the main engine current is 142.5A.
[0098] Example 5
[0099] This embodiment provides a glass fiber reinforced nylon composite material, the raw materials for preparing the composite material include the following components in parts by weight:
[0100]
[0101]
[0102] The preparation method of the glass fiber reinforced nylon composite material comprises the following steps:
[0103] (1) Dry PA6, glass fiber exposed absorbent, super dispersant, toughening agent, organic black masterbatch, antioxidant and lubricant at 80°C for 2 hours;
[0104] (2) The dried raw materials in step (1) are dry-mixed in a high-speed mixer at 30°C for 2 minutes, then added to a twin-screw extruder, mixed with modified glass fiber (diameter 17 μm) treated with coupling agent KH550, melt-extruded at 230-265°C, and granulated to prepare the glass fiber reinforced nylon composite material. The temperature settings of the heating zones of the screw are: 263°C for zone 1, 253°C for zone 2, 255°C for zone 3, 245°C for zone 4, 250°C for zone 5, 235°C for zone 6, 235°C for zone 7, 240°C for zone 8, and 232°C for zone 9; the main engine speed is 520rpm, and the main engine current is 180A.
[0105] Example 6
[0106] This embodiment provides a glass fiber reinforced nylon composite material, the raw materials for preparing the composite material include the following components in parts by weight:
[0107]
[0108]
[0109] The preparation method of the glass fiber reinforced nylon composite material comprises the following steps:
[0110] (1) Dry PA6, glass fiber exposed absorbent, dispersant, toughening agent, organic black masterbatch, antioxidant and lubricant at 80°C for 2 hours;
[0111] (2) The dried raw materials in step (1) are dry-mixed in a high-speed mixer at 20°C for 3 minutes, then added to a twin-screw extruder, mixed with modified glass fiber (diameter 11 μm) whose surface is treated with coupling agent KH300, melt-extruded at 230-265°C, and granulated to prepare the glass fiber reinforced nylon composite material. The temperature settings of each heating zone of the screw are: 260°C for zone 1, 250°C for zone 2, 260°C for zone 3, 240°C for zone 4, 240°C for zone 5, 230°C for zone 6, 230°C for zone 7, 230°C for zone 8, and 235°C for zone 9; the main engine speed is 500rpm, and the main engine current is 130A.
[0112] Example 7
[0113] This embodiment provides a glass fiber reinforced nylon composite material, the raw materials for preparing the composite material include the following components in parts by weight:
[0114]
[0115] The preparation method of the glass fiber reinforced nylon composite material comprises the following steps:
[0116] (1) Dry PA6, glass fiber exposed absorbent, super dispersant, toughening agent, organic black masterbatch, antioxidant and lubricant at 80°C for 2 hours;
[0117] (2) The dried raw materials in step (1) are dry-mixed in a high-speed mixer at 25°C for 2 minutes, then added to a twin-screw extruder, mixed with modified glass fiber (diameter 13 μm) whose surface is treated with coupling agent KH550, melt-extruded at 230-265°C, and granulated to prepare the glass fiber reinforced nylon composite material. The temperature settings of each heating zone of the screw are: 260°C for zone 1, 250°C for zone 2, 260°C for zone 3, 240°C for zone 4, 240°C for zone 5, 230°C for zone 6, 230°C for zone 7, 230°C for zone 8, and 235°C for zone 9; the main engine speed is 500rpm, and the main engine current is 165A.
[0118] Example 8
[0119] This embodiment provides a glass fiber reinforced nylon composite material, which differs from Example 1 in that the hyperdispersant is replaced by a dispersant (Songou S310), and other raw materials, contents and preparation methods are the same as those in Example 1.
[0120] Example 9
[0121] This embodiment provides a glass fiber reinforced nylon composite material, which differs from Example 1 in that the toughening agent is replaced by a toughening agent (Weishang B840), and other raw materials, contents and preparation methods are the same as those in Example 1.
[0122] Example 10
[0123] This embodiment provides a glass fiber reinforced nylon composite material, which differs from Example 1 in that the organic black masterbatch is replaced by an inorganic black masterbatch (Huihong HH9350), and other raw materials, contents and preparation methods are the same as those in Example 1.
[0124] The preparation methods of Examples 11-14 and Comparative Examples 1-6 are the same as that of Example 1, and the weight proportions of the corresponding raw material components are shown in Table 1.
[0125] Table 1
[0126]
[0127] The above-mentioned Examples 1-14 and Comparative Examples 1-6 were subjected to performance tests, and the performance evaluation method and implementation standards were as follows:
[0128] The glass fiber reinforced nylon composite materials obtained in Examples 1-14 and Comparative Examples 1-6 were first dried in a blast oven at 80°C for 4 hours, and then the dried glass fiber reinforced nylon composite materials were injection molded on an injection molding machine to prepare samples. The injection molding mold temperature was controlled at about 80°C.
[0129] The sample sizes according to ISO standards are:
[0130] Tensile specimen: ISO 527, specimen is 1B type specimen;
[0131] Bending specimen: ISO 178, specimen size: 80×10×4mm;
[0132] Izod notched impact specimen: ISO 179, specimen size 80×10×4mm;
[0133] Melt index: ISO 1183, 275°C / 2.16kg.
[0134] The prepared samples are then tested and analyzed for relevant properties according to the corresponding test standards. The comprehensive mechanical properties of the material are judged by the values of tensile strength, elongation at break, flexural strength, flexural modulus and impact strength obtained by the test; the molding flow properties of the material are judged by the value of the melt index of the material measured under the above conditions.
[0135] The test results are shown in Table 2.
[0136] Table 2
[0137]
[0138] The test results show that:
[0139] (1) The present invention compounds glass fiber exposed absorbent, dispersant, toughening agent and black masterbatch, and adds them to a glass fiber reinforced nylon material composed of nylon and glass fiber, so that the obtained glass fiber reinforced nylon composite material can have high fluidity and high toughness while ensuring good mechanical strength.
[0140] (2) By comparing Example 1 with Examples 8-10, it can be seen that the present invention can improve the comprehensive properties of the obtained glass fiber reinforced nylon composite material, such as impact strength, elongation at break and flexural modulus, by further optimizing the dispersant, toughening agent and black masterbatch.
[0141] (3) By comparing Example 1 with Examples 11-14, it can be seen that in Example 13, the proportions of the dispersant and the toughening agent are reduced, so that the mass ratio of the glass fiber exposed absorbent, the dispersant and the toughening agent exceeds the range of 1:(1-4):(10-25). Although the fluidity of the obtained glass fiber reinforced nylon composite material is significantly improved, its impact strength and flexural modulus are significantly reduced, and the elongation at break is also reduced; in Example 14, the proportions of the dispersant and the toughening agent are increased, which also makes the mass ratio of the glass fiber exposed absorbent, the dispersant and the toughening agent exceed the range of 1:(1-4):(10-25). The impact strength, flexural modulus and melt index of the obtained glass fiber reinforced nylon composite material are significantly reduced, and the elongation at break is also reduced; This shows that the present invention can better improve the comprehensive performance of the obtained glass fiber reinforced nylon composite material in terms of toughness, fluidity and mechanical strength by further limiting the mass ratio of the glass fiber exposed absorbent, the dispersant and the toughening agent, thereby obtaining a product with better comprehensive performance.
[0142] (4) By comparing Example 1 with Comparative Examples 1-3, it can be seen that the lack of any one of the components of the glass fiber exposed absorbent, dispersant and toughening agent will result in poor comprehensive performance (toughness, mechanical strength and fluidity) of the obtained glass fiber reinforced nylon composite material, which indicates that the glass fiber exposed absorbent, dispersant and toughening agent in the technical solution provided by the present invention can play a synergistic effect, so that the obtained glass fiber reinforced nylon composite material has high fluidity and high toughness while maintaining a certain mechanical strength.
[0143] (5) By comparing Example 1 with Comparative Example 4, it can be seen that the addition of black masterbatch can improve the fluidity and toughness of the obtained glass fiber reinforced nylon composite material to a certain extent, thereby obtaining a product with better comprehensive performance.
[0144] (6) By comparing Example 1 with Comparative Examples 5 and 6, it can be seen that the selection of the specific glass fiber exposed absorbent content is beneficial to improving the fluidity and toughness of the obtained glass fiber reinforced nylon composite material. When its content is less than 0.1 parts by weight, the fluidity of the obtained product cannot be well improved. When its content is higher than 0.5 parts by weight, its fluidity is too high, and the tensile strength and bending strength are significantly deteriorated, which is not conducive to injection molding.
[0145] In summary, the present invention can effectively solve the technical problem of reduced fluidity and toughness of the obtained nylon composite material due to the addition of high content of glass fiber by selecting and matching specific raw materials and their contents, thereby achieving a high-fluidity and high-toughness glass fiber reinforced nylon composite material by adding only a small amount of glass fiber exposed absorbent, dispersant, toughening agent and black masterbatch and other components. Not only is the preparation process simple and easy to operate, but the production cost is also effectively reduced, thereby expanding the application field of nylon composite materials and having strong practical value.
[0146] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A glass fiber reinforced nylon composite material, characterized in that: The raw materials for preparing the glass fiber reinforced nylon composite material include the following components in parts by weight:
2. The glass fiber reinforced nylon composite material according to claim 1, characterized in that: The mass ratio of the glass fiber exposed absorbent, dispersant and toughening agent is 1:(1-4):(10-25).
3. The glass fiber reinforced nylon composite material according to claim 1 or 2, characterized in that: The glass fiber exposed absorbent includes any one of ethylene bis stearic acid amide, modified ethylene bis fatty acid amide or polytetrafluoroethylene or a combination of at least two thereof, preferably modified ethylene bis fatty acid amide; Preferably, the dispersant includes any one of a fatty acid dispersant, a pentaerythritol ester dispersant or a silicone dispersant or a combination of at least two thereof, preferably a silicone dispersant; Preferably, the toughening agent comprises any one or a combination of at least two of polyolefin elastomer, styrene-butadiene-styrene block copolymer, ethylene propylene diene monomer rubber, methacrylate / butadiene / styrene copolymer or maleic anhydride grafted polyolefin elastomer, preferably maleic anhydride grafted polyolefin elastomer.
4. The glass fiber reinforced nylon composite material according to any one of claims 1 to 3, characterized in that: The viscosity of the nylon is 2.45-2.
55.
5. The glass fiber reinforced nylon composite material according to any one of claims 1 to 4, characterized in that: The modified glass fiber is a glass fiber treated with a coupling agent; Preferably, the coupling agent comprises a silane coupling agent; Preferably, the silane coupling agent includes γ-aminopropyltriethoxysilane; Preferably, the diameter of the glass fiber is 11-17 μm; Preferably, the length of the glass fiber is 13 μm.
6. The glass fiber reinforced nylon composite material according to any one of claims 1 to 5, characterized in that: The auxiliary agents include antioxidants and lubricants.
7. The glass fiber reinforced nylon composite material according to claim 6, characterized in that: The antioxidant includes a hindered phenol antioxidant and / or a phosphite antioxidant; Preferably, the content of the antioxidant is 0.1-0.8 parts by weight; Preferably, the lubricant comprises stearic acid amide; Preferably, the content of the lubricant is 0.2-1 parts by weight.
8. A method for preparing a glass fiber reinforced nylon composite material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The glass fiber reinforced nylon composite material is obtained by mixing nylon, glass fiber exposed absorbent, dispersant, black masterbatch, toughening agent and auxiliary agent, adding modified glass fiber, melting and extruding, and granulating.
9. The method for preparing a glass fiber reinforced nylon composite material according to claim 8, characterized in that: The nylon, glass fiber exposed absorbent, dispersant, black masterbatch, toughening agent and additives are dried before mixing; Preferably, the drying temperature is 75-85°C; Preferably, the drying time is 1-2h; Preferably, the mixing temperature is 20-30°C; Preferably, the mixing is carried out under stirring; Preferably, the stirring time is 2-3 min; Preferably, the melt extrusion is carried out in a twin-screw extruder; Preferably, the temperature settings of the heating zones of the twin-screw extruder are: zone 1 260-265°C, zone 2 250-260°C, zone 3 250-260°C, zone 4 240-250°C, zone 5 240-250°C, zone 6 230-240°C, zone 7 230-240°C, zone 8 230-240°C, zone 9 230-235°C; Preferably, the main engine speed of the twin-screw extruder is 450-520rpm; Preferably, the main engine current of the twin-screw extruder is 130-180A.
10. Use of the glass fiber reinforced nylon composite material according to any one of claims 1 to 7 in electric tools and automobile parts.
Citation Information
Patent Citations
Polyamide 6 composite and preparation method thereof
CN101983988B
Heat conducting nylon plastic and method for preparing same
CN106916443A